effect of slenderness ratio in the kinematics of the rotational flow with rigid boundaries (Nexo Revista Científica, 2015)
In this work we analyse the components of the radial velocity (u), azimuthal (v), primary and secondary volumetric flows, (Qp), and (Qs), and the torque coefficient (Cm), all of which are produced inside a closed cylinder which has a rotary lid and the bottom and wraparound surface are static. The results are graphically presented, considering a Reynolds number laminar of 3x104 and for container form factors (height/radius) of 1.0, 1.25, 1.5, 1.75, and 2.0. Starting from a geometric ratio of 1.0 and comparing it to the rest of form factors, it was observed that the radial velocity component (u) increased its maximum positive value in a 14.02 %; the tangential velocity component kept the same maximum values in all the geometric ratios; the primary volumetric flow increased by 193.25 %; the secondary volumetric flow increased by 236.48 %; and the torque coefficient also increased by 94.41 %. These results imply that in modifying the slenderness ratio of the system, the studied kinematic properties do not follow an homogeneous variation pattern and depending on the concern of each of them, its behaviour should be analysed in detail.